2019
DOI: 10.1002/ieam.4131
|View full text |Cite
|
Sign up to set email alerts
|

Water reuse as an incentive to promote sustainable agriculture in Lebanon: Stakeholders’ perspectives

Abstract: While technical and economic feasibility of water reuse projects is requisite for implementation, issues in relation to cultural values, public acceptability, and perceptions should not be marginalized. This research focuses on examining the Lebanese stakeholders’ knowledge, perception, and attitude toward the reuse of treated wastewater and on exploring potential enabling factors. Accordingly, in‐depth interviews were conducted with stakeholders from concerned ministries, Lebanese Farmers Syndicate, farmers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 28 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Combining the obtained results, it can be concluded that the TWW reuse promotion and enhancement is required to overcome the lack of adequate information about benefits (Massoud et al 2019), incomplete economic analysis of TWW reuse options, misalignment between water prices and water scarcity, and lack of economic incentives for reuse (Frascari et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Combining the obtained results, it can be concluded that the TWW reuse promotion and enhancement is required to overcome the lack of adequate information about benefits (Massoud et al 2019), incomplete economic analysis of TWW reuse options, misalignment between water prices and water scarcity, and lack of economic incentives for reuse (Frascari et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Attitude is the first TBP variable that affects behavioral intention (44). Any behavior is more likely to occur when a person has a positive attitude toward it (28,(45)(46)(47)(48)(49). On the other hand, if a person finds it useful to do something, they do it, and if they find the behavior harmful, they refuse to do it (50).…”
Section: Attitudementioning
confidence: 99%
“…In exploring research identifying potential barriers towards dealing with wastewater that links to socio-political and legal barriers which relate to uptake of wastewater reuse, for example, in Lebanon, research on a community on water reuse acceptance found that most of the population had more trust in their own judgement rather than any scientific evidence that was presented to them [37], and re-shaping this population judgement can be critical for overcoming the 'yuck' factor perceived by consuming products with large quantities of wastewater [38]. Gaining the acceptance and trust of the population may become more effective in driving wastewater reuse than through technical advancement alone [39], whilst an effective political and legal regime with well thought-out, designed and implemented political objectives and regulations can help to remove barriers to implementation and present opportunities to adopters of change [40,41]. Therefore, in designing frameworks for circular water systems with increased wastewater use, there is a need to consider barriers and opportunities relating to political, economic, social, technological, environmental and legal contexts.…”
Section: Opportunities Barriers and The Pestel Frameworkmentioning
confidence: 99%
“…Furthermore, data availability throughout a project and transparency of the operations of the wastewater treatment plants (WWTPs) could be a good starting point in gaining people's acceptance and trust. As a result, distrust of the farmers and susceptibility towards the level of treatment of the wastewater would ameliorate, leading to the broader acceptance of the practice [39,61]. Furthermore, the degree of stakeholders' acceptance influences the local authorities' capability for implementing such projects.…”
Section: Social Aspectsmentioning
confidence: 99%
See 1 more Smart Citation